Biohybrid device with antagonistic skeletal muscle tissue for measurement of contractile force. (4th March 2019) - Morimoto, Yuya; Onoe, Hiroaki; Takeuchi, Shoji
ABSTRACT: This paper describes a fabrication method and driving property of a biohybrid device with an antagonistic pair of skeletal muscle tissues and a flexible substrate. Since two skeletal muscle tissues are symmetrically arranged with the flexible substrate as the central axis, the flexible substrate deforms according to differences in their tension. In the formation of the antagonistic pair of skeletal muscle tissues, we assembled myoblast-laden hydrogel sheets and cultured them to construct a single skeletal muscle tissue on each side of the flexible substrate. We confirmed that the skeletal muscle tissue on the flexible substrate had the fundamental morphology and function of skeletal muscle. Furthermore, we made the biohybrid device actuate with deformation of the flexible substrate by selective contractions of the skeletal muscle tissues. From the deformation of the flexible substrate, we estimated the contractile force of each skeletal muscle tissue in the biohybrid device using finite element analysis. This biohybrid device, composed of an antagonistic pair of skeletal muscle tissues and a flexible substrate, can potentially be used in biological studies and pharmacokinetic assays involving the antagonistic pair of skeletal muscles. GRAPHICAL ABSTRACT: